Capital Structure, Business Risk and Company Value with Firm Size as a Moderating Variable: Empirical Evidence from Pharmaceutical Companies in Indonesia - Anisah, Anisah; Murad, Moh. Ali; Asriadi, Asriadi; Samudra, Suryadi; Magfirah, Dilah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study investigates the extent to which firm size can strengthen or weaken the relationship between capital structure and business risk in inducing firm value. This study uses panel data from ten pharmaceutical companies sourced from the company's annual reports for 2015-2021. The data analysis technique used the Structure Equation Modeling (SEM) method through the Partial Least Square (PLS) approach with WarpPLS 6.0 software. This study found that capital structure had no effect on firm value, while business risk had a significant negative effect on firm value. Firm size is only able to moderate the relationship between capital structure and firm value. Thus, in order to maximize the value of pharmaceutical companies in Indonesia, the main concern of managers is to ensure that the amount of income received by the company remains stable in order to avoid income volatility that can trigger increased business risk for the company. In addition, it is also necessary to consider the size of the company when you want to make a policy to determine how much debt or equity is used to finance the company so that maximizing the value of the company can be achieved.